The Effects of Climate Change on Rural Livestock Farming: Evidence from Limpopo Province, South Africa - Maluleke, Witness; Tshabalala , Ntwanano Patrick; Barkhuizen , Jaco (Asian Journal of Agriculture and Rural Development, 2020)
The objective of this study is to identify the perceptions of the conspicuous rural livestock farmers as well as the officials from the Department of Agriculture, Forestry and Fisheries (DAFF) on the effects of climate change on rural livestock farming practices. From a qualitative standpoint, this study purposively selected participants from Limpopo Province, focusing on Giyani, Lenting, Ga-Mphahlele and Malamulele areas comprising of rural livestock farmers [12:3 = 36] and DAFF officials [6:2]. Overall, 42 participants formed part of this study through Face-to-Face and Focus Group Discussions. It is found that the loss and damage related to the contrary effects of climate change are insufficiently applied in the chosen rural areas of Limpopo Province. The local and regional collaborations by the responsible spheres of government are not strengthened and promoted, leading to inefficient strategies and approaches to addressing related conditions. Therefore, the significance of risk transmission and dissemination via regional cooperation regarding climate change adaptation are pivotal in rural settings.